Cross-Sector Communication Strategy in Supporting the Implementation of the Food Security and Free Nutritious Meals (MBG) Program in Majene Regency - Muhammad Sulthan; Muhammad Sajidin (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2026)
This study aims to analyze cross-sector communication strategies to support the implementation of the Free Nutritious Meals Program (MBG) while strengthening food security in Majene Regency. As a new national program requiring multi-actor coordination, the MBG faces potential information and perception gaps between actors, necessitating planned cross-sector communication. This study used a case study method with a qualitative approach through in-depth interviews, field observations, and policy document reviews. The results show that communication practices involve three main actors: the local government, food businesses and UMKM, and local communities including farmer groups and PKK cadres. Initially, communication patterns were formal and one-way through coordination meetings but have since transformed into faster and more responsive digital communication. Several challenges were encountered, including limited communication infrastructure in remote areas, differing interests in the food supply chain, and low public nutrition literacy, which results in uneven absorption of policy messages. To address these challenges, the local government implemented four communication strategies: an information strategy to expand dissemination, a participatory strategy through village deliberations and community involvement, a collaborative strategy with the private sector and civil society organizations, and an education strategy to improve nutritional understanding and encourage behavioral change. These findings confirm that the success of the MBG program lies not only in the distribution of nutritious food, but also in the synergy of communication between actors to build an inclusive, sustainable, and local potential-based food ecosystem.